PENGARUH INFLASI DAN SUKU BUNGA TERHADAP RETURN SAHAM MANUFAKTUR SEKTOR INDUSTRI DI BEI PERIODE 2018-2023 - Lestari, Lia Wulan; Saparuddin M, Saparuddin M (Bhinneka Multidisiplin Journal, 2025)
Stocks as an economic instrument are now becoming a favorite among the public, especially attracting high attention from young people or millennials. Factors that can affect stock returns are economic conditions, inflation, interest rates, dividends, company performance and so on. Therefore, inflation and interest rate factors play a key role in influencing stock returns, high inflation can harm company profitability and people's purchasing power. A hypothesis suggests that inflation has a negative effect on stock returns. On the other hand, low interest rates can stimulate investment and economic growth. This research is a quantitative study to develop and use mathematical models, theories, or hypotheses related to other phenomena. This article conducts research on "The effect of inflation and interest rates on stock returns in the manufacturing sector of the industry on the IDX." The results of the study show that the inflation variable has a greater effect on stock returns compared to the interest rate variable. Inflation is more capable of explaining its effect on stock returns, because its effect is more stable and more measurable in the long term.